2019
DOI: 10.1186/s12879-019-4149-2
|View full text |Cite
|
Sign up to set email alerts
|

Actinomyces neuii: a case report of a rare cause of acute infective endocarditis and literature review

Abstract: Background Infective endocarditis caused by Actinomyces spp. is extremely rare. However, cases by new species of Actinomyces have been increasingly reported due to advances in laboratory techniques, and many of these species do not cause classic presentations of actinomycosis. Actinomyces neuii is reported to have a tendency to cause endovascular infection. The course of infective endocarditis caused by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 46 publications
1
17
0
2
Order By: Relevance
“…11,12 A previous study has demonstrated the performance of MALDI-TOF MS in identification of endocarditis due to A neuii . 13 As in this case, MALDI-TOF MS was used to confirm the etiologic organism in subacute endocarditis.…”
Section: Discussionmentioning
confidence: 93%
“…11,12 A previous study has demonstrated the performance of MALDI-TOF MS in identification of endocarditis due to A neuii . 13 As in this case, MALDI-TOF MS was used to confirm the etiologic organism in subacute endocarditis.…”
Section: Discussionmentioning
confidence: 93%
“…Treatments were heterogeneous as well, including surgical debridement and oral, intravenous and intraperitoneal antibiotics. Only 1 of 20 reported cases resulted in death 21‐39 …”
Section: Discussionmentioning
confidence: 99%
“…Actinomyces neuii je stanovnik normalne mikroflore kože i sluzokože i to pogotovo oralne sluznice (kao i većina sojeva aktinomiceta i korinebakterija) [2]. Ipak, u studijama koje su uklјučene u ovaj sistematski pregledni članak pokazano je da A. neuii može izazvati endokarditis [9,17,22], endoftalmitis [8,26,28,29,30], osteomijelitis [15], pleuralni empijem [24], apsces [6,7,10,21], neonatalnu sepsu [14,23], peritonitis [18,27], infekcije ventrikuloperitonealnog šanta [13,19], infekcije periprostetičkog tkiva [16], infekcije proteze i okolnog tkiva [20,25].…”
Section: Slika 4 Antibiotici Korišćeni U Lečenju Infekcija Uzrokovanunclassified
“…neuii može biti deo normalne flore čoveka, i kao takva najčešće obitava u usnoj duplјi ili u urogenitalnom traktu [2]. Najčešće izaziva infekcije mekih tkiva i lezije na koži [6], 5apscese [7], edoftalmitis [8], enokarditis [9], bakterijemiju [10], a mogući je i izazivač perikarditisa, osteomijelitisa i horioamnionitisa [5,11]. Ne postoje dokazi da starost ili broj godina utiču značajno na razliku u učestalosti inficiranja ovim uzročnikom, ali sigurno je da Acinetobacter neuii češće prouzrokuje obolјenja kod imunokompromitovanih pacijenata.…”
unclassified